Deep‐Sea Hydrothermal Fields as Natural Power Plants. Issue 16 (4th June 2018) - Yamamoto, Masahiro; Nakamura, Ryuhei; Takai, Ken
Abstract: Deep‐sea hydrothermal vents are hot springs on the seafloor. In recent years, electricity generation in deep‐sea hydrothermal vents has been reported. Electricity can be generated through the sulfide minerals that form in seafloor hydrothermal deposits, and these minerals can convert the redox and heat energy between hydrothermal fluids and seawater into electric power. The physical and chemical phenomena of generating electricity from natural minerals provide key insights into development of deep‐sea power plants and novel electricity‐conversion materials with earth abundant elements. In addition, the new findings have established a novel concept of life, e. g., existence of electricity‐sustained life in hydrothermal vents and widespread occurrence of electron‐uptake ecosystems on the seafloor, together with a new hypothesis about the origin of life. Abstract : Nature's deep‐sea electrochemical reactors : electricity is generated between hydrothermal fluids and seawater via conductive sulfide mineral deposits in deep‐sea hot vents. The power generation proposes some interesting hypothesis related with electricity‐driven ecosystems and prebiotic metabolism evolution, not only on Earth but on other worlds.